2019
DOI: 10.1186/s13046-019-1311-z
|View full text |Cite
|
Sign up to set email alerts
|

Nek2 augments sorafenib resistance by regulating the ubiquitination and localization of β-catenin in hepatocellular carcinoma

Abstract: Background Sorafenib is the first-line treatment for advanced-stage hepatocellular carcinoma (HCC). Several studies have shown that the up-regulation of β-catenin plays a role in sorafenib resistance in HCC; however, the mechanism associated with this phenomenon remains elusive. Methods Western blotting, flow cytometry, and an evaluation of IC 50 values were used to confirm the role of β-catenin in HCC sorafenib resistance. Immunoprecipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 30 publications
(10 reference statements)
1
22
0
Order By: Relevance
“…Breast cancer Paclitaxel or Gemcitabine [70] HIF-dependent BMX kinase upregulation resulted in therapeutic resistance through a compensatory pro-survival signaling mechanism Acute myeloid leukemia Sorafenib [197] HIF2 and COX2 activated Snail and downregulated E-cadherin expression to promote invasion and resistance to sorafenib Renal cancer Sorafenib [198] HIF-2α activated TGF-α/EGFR pathway to promote proliferation and sorafenib-resistance, which was antagonized by HIF-2α siRNA Hepatocellular carcinoma Sorafenib [199] Prospero-related homeobox 1 (PROX1) upregulated β-catenin transcription and nuclear translocation to activate the Wnt/β-catenin pathway in HCC, which lead to high proliferation and sorafenib-resistance Hepatocellular carcinoma Sorafenib [209] Nek2 stabilized β-catenin, increased its nuclear translocation, and activated the transcription of its downstream target genes, to promote sorafenib-resistance Hepatocellular carcinoma Sorafenib [210] Suppression of checkpoint kinase 1 (CHK1) pathway by Wnt/β-catenin in p53 wild-type colorectal cancer cells, promoted drug-resistance Colorectal cancer 5-Fluorouracil [211] IL-6/p-STAT3 activation increased the expression of DNMT3b/OCT4 which conferred early recurrence and poor prognosis in HCC Hepatocellular carcinoma Sorafenib [215] The expression of Sox2 and CD24 were upregulated in targeted-therapy resistant melanoma cells, which was mediated by activated STAT3. Activation of STAT3, Sox2 and CD24 promoted adaptive-resistance to BRAF inhibitors.…”
Section: Ap1mentioning
confidence: 99%
“…Breast cancer Paclitaxel or Gemcitabine [70] HIF-dependent BMX kinase upregulation resulted in therapeutic resistance through a compensatory pro-survival signaling mechanism Acute myeloid leukemia Sorafenib [197] HIF2 and COX2 activated Snail and downregulated E-cadherin expression to promote invasion and resistance to sorafenib Renal cancer Sorafenib [198] HIF-2α activated TGF-α/EGFR pathway to promote proliferation and sorafenib-resistance, which was antagonized by HIF-2α siRNA Hepatocellular carcinoma Sorafenib [199] Prospero-related homeobox 1 (PROX1) upregulated β-catenin transcription and nuclear translocation to activate the Wnt/β-catenin pathway in HCC, which lead to high proliferation and sorafenib-resistance Hepatocellular carcinoma Sorafenib [209] Nek2 stabilized β-catenin, increased its nuclear translocation, and activated the transcription of its downstream target genes, to promote sorafenib-resistance Hepatocellular carcinoma Sorafenib [210] Suppression of checkpoint kinase 1 (CHK1) pathway by Wnt/β-catenin in p53 wild-type colorectal cancer cells, promoted drug-resistance Colorectal cancer 5-Fluorouracil [211] IL-6/p-STAT3 activation increased the expression of DNMT3b/OCT4 which conferred early recurrence and poor prognosis in HCC Hepatocellular carcinoma Sorafenib [215] The expression of Sox2 and CD24 were upregulated in targeted-therapy resistant melanoma cells, which was mediated by activated STAT3. Activation of STAT3, Sox2 and CD24 promoted adaptive-resistance to BRAF inhibitors.…”
Section: Ap1mentioning
confidence: 99%
“…SMAC was not identified as hub-gene in the M1 module. NEK2 plays a role in developing drug resistance against various anti-cancer drugs, including 5-fluorouracil and sorafenib [ 69 , 96 , 97 ]. A potential role of NEK2 in resistance development against lenvatinib and other anti-angiogenic drugs has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…NEK2 is associated with drug resistance in multiple cancers 13 , and several publications have shown regulation of NEK2 by antitumor drugs. Deng's research demonstrated that NEK2 binds β-catenin, blocking the interaction between NEK2 and the destruction complex; ultimately contributing to sorafenib resistance in hepatocellular carcinoma 20 . In Wen's study, overexpression of NEK2 in cancer cells resulted in enhanced chromosomal instability, cellular proliferation, and drug resistance; while NEK2 knockdown overcame cancer cell resistance to drugs and induced apoptosis in vitro and in a xenograft myeloma mouse model 21 .…”
Section: Discussionmentioning
confidence: 99%